PERAN PUSAT PELAYANAN TERPADU PEMBERDAYAAN PEREMPUAN DAN ANAK (P2TP2A) KOTA PEKANBARU DALAM PENANGANAN ANAK YANG BERHADAPAN DENGAN HUKUM (ABH) TAHUN 2013-2014 - Dewi Putri Anggi; Muchid " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Children are gift from Allah SWT, They are the next generation of the nationwho are protected by state and government and still in growth phsyically and mentally.However, in daily activity, sometimes children face the difficult situations that makethem breaking and dealing with the law, and this is known as ABH. When the childrenare processed by the law then they will be subject of the article of child criminal lawwith imprisonment as the consequences. As a prisoner, children will be losing physicalfreedom, losing of control over life, losing of family, losing of goods and services,losing of security, lack of stimulation and psychological disturbance.This research aims to see how the role of P2TP2A Pekanbaru City in handlingABH and see what factors are inhibiting P2TP2A Pekanbaru City in doing it’s role.This research uses the role theory and policy implementation by Geode Edward III.This research is guided by qualitative explanation. This result shows that the role ofP2TP2A Pekanbaru City in handling ABH has not been accomplished maximally yet. Asfor factors that inhibit P2TP2A in implementing the role are human resources, budget,and facilities.Keywords: role, P2TP2A, ABH.